Gluon condensation and scaling exponents for the propagators in Yang-Mills theory - Eichhorn, Astrid; Gies, Holger; Pawlowski, Jan M. (Arxiv, 2011)
We investigate the infrared (strong-coupling) regime of SU(N)-Yang-Mills theory on a self-dual background. We present an evaluation of the full effective potential for the field strength invariant F_{μ ν}F^{μ ν} from non-perturbative gauge correlation functions and find a non-trivial minimum corresponding to the existence of a dimension four gluon condensate in the vacuum. We also relate the infrared asymptotic form of the beta function of the running background-gauge coupling to the asymptotic behavior of Landau-gauge gluon and ghost propagators. Consistency between both gauges in the infrared imposes a new upper bound on the infrared exponents of the propagators. For the scaling solution, this bound reads kappa_c < 23/38 which, together with Zwanziger's horizon condition kappa_c> 1/2, defines a rather narrow window for this critical exponent. Current estimates from functional methods indeed satisfy these bounds.